1990
DOI: 10.1056/nejm199008233230801
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind Study of Phenytoin for the Prevention of Post-Traumatic Seizures

Abstract: Phenytoin exerts a beneficial effect by reducing seizures only during the first week after severe head injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
426
3
8

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 895 publications
(450 citation statements)
references
References 16 publications
13
426
3
8
Order By: Relevance
“…Phenytoin had the most robust effects of the tested anticonvulsants, but resistance eventually developed (Fig. 3C and previous results30), as occurs after human brain injury 55. Thus, many drugs with robust anticonvulsant but not antiepileptogenic effects would be missed in this screen.…”
Section: Discussionmentioning
confidence: 63%
“…Phenytoin had the most robust effects of the tested anticonvulsants, but resistance eventually developed (Fig. 3C and previous results30), as occurs after human brain injury 55. Thus, many drugs with robust anticonvulsant but not antiepileptogenic effects would be missed in this screen.…”
Section: Discussionmentioning
confidence: 63%
“…The only study that showed a prophylactic effect of PHT in preventing PTE was not blinded [2]. Paradoxically, three studies showed a higher incidence of PTE in patients receiving PHT or PB than in untreated groups [16][17][18].…”
Section: Results Of Randomized Clinical Trials For Prophylaxismentioning
confidence: 99%
“…In addition, several lines of evidence from animal studies suggest that AEDs might interfere with the recovery of brain function after TBI [19]. However, in clinical study, it is difficult to tease out AED cognitive side effects from the direct effects of TBI and from AED inhibition of recovery of brain function after TBI [17].…”
Section: Potential Pitfalls Of Using or Not Using Aed Prophylaxis Aftmentioning
confidence: 99%
“…Neither of these trials was able to identify an anti-epileptogenic effect. A number of the early studies purported to show positive effects of phenobarbital and PHT, but more recent randomized controlled trials (RCTs) have demonstrated no useful effects [14] and even suggested that there were additional cognitive side effects associated with these treatments [16]. Similarly, the 1 well-performed RCT with valproic acid also failed to show any beneficial effect [15].…”
Section: Lessons From Epilepsy Prevention Trials Using Asdsmentioning
confidence: 99%
“…Five studies used phenytoin (PHT) alone, 5 used PHT and phenobarbital, and 1 each used phenobarbital, carbamazepine, or valproic acid. Only the 2 performed at the University of Washington (1 PHT [14] and 1 valproic acid [15]) were randomized, double-blind, controlled trials, and these were the 2 trials with the largest number of enrolled participants. Neither of these trials was able to identify an anti-epileptogenic effect.…”
Section: Lessons From Epilepsy Prevention Trials Using Asdsmentioning
confidence: 99%